Bone Hook Reduction Technique Combined with Lateral Parapatellar Arthrotomy for Periprosthetic Distal Femoral Fractures Following Total Knee Arthroplasty: A Technical Note. Issue 8 (22nd June 2022) - Shon, Oog‐Jin; Kim, Gi Beom; On, Je Won
Abstract : Objective: To report a bone hook reduction technique combined with lateral parapatellar arthrotomy for periprosthetic distal femoral fractures following total knee arthroplasty (TKA). Methods: From April 2012 to June 2018, a total of 31 knees who underwent this technique for the treatment of periprosthetic distal femoral fractures following TKA were retrospectively reviewed. Through a lateral parapatellar arthrotomy, the vastus lateralis fascia was dissected from the muscle belly to allow anteromedial mobilization of the muscles. With direct visualization of the posteriorly angulated distal fragment, a bone hook was placed on the anterior flange of the femoral component. The hook was then elevated to correct the posteriorly angulated and shortened distal fragment. The coronal and sagittal alignments of the distal segment with the femoral shaft were confirmed using fluoroscopic images, and internal fixation was performed using an anatomically pre‐contoured lateral locked plate. Once the overall length and sagittal plane alignment were restored, the plate was inserted via the previous articular approach. The plate was centered on the femur using anteroposterior and lateral fluoroscopy and then fixed. Results: A total of 28 patients underwent internal fixation using the bone hook reduction technique combined with lateral parapatellar arthrotomy for the treatment of periprosthetic distal femoral fractures following TKA. The average age at operation was 70.9 years (range, 62–83 years), and the average follow‐up period was 17.5 months (range, 12–48.5 months). Fractures were classified as Su type I (13/28 [46.4%]), type II (11/28 [39.3%]), and type III (4/28 [14.3%]). Bone union was confirmed radiographically in all patients. Conclusion: The bone hook reduction technique is a simple and effective method to reduce the distal fragment in periprosthetic distal femoral fractures following TKA. Abstract : The bone hook could be applied to the anterior femoral flange with minimal lateral parapatellar arthrotomy. A bone hook is placed on the anterior flange of the femoral component. The hook is then elevated to correct the posterior angulation and shortening of the distal fragment.